A case of mistaken arrhythmogenic identity during pregnancy. Issue 8 (6th August 2021) - Asher, Clint; Thomas, Tessa; Rinaldi, Christopher A.; Carr‐White, Gerry
Abstract: Atypical LVOT ectopy can present with an RVOT morphology on ECG and differentiation to reveal this focus is in favor of benign idiopathic ventricular ectopy over an arrhythmogenic cardiomyopathy. Abstract : Atypical LVOT ectopy can present with an RVOT morphology on ECG and differentiation to reveal this focus is in favor of benign idiopathic ventricular ectopy over an arrhythmogenic cardiomyopathy.